2016
DOI: 10.1177/0193723516632574
|View full text |Cite
|
Sign up to set email alerts
|

Sport for Development and Peace in Action

Abstract: The aim of this article is to provide insight on how claims that sport contributes to development or peace are transformed into facts. Beyond a theoretical discussion about how sport for development and peace (SDP) facts are built, this article demonstrates, in rich detail, the subtle art of SDP fact building for funding purposes. Specifically, through an integrative literature review and two case studies, a mix of fact-building actors composed of experts, literature, and allies, is exposed and analyzed. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…For example, in their own research on SDP organizations in Kingston, Jamaica, Darnell et al (2018a) found that an organization that had traditionally dealt with health and HIV/AIDS prevention turned its focus to sport when this opened up the possibility of obtaining funding and expertise from a UK-based international NGO. In effect, actors such as money, expertise, technical support, ‘and even the concept of sport’s development utility’ (Darnell et al, 2018a: 95) played a part in holding SDP together – and in revealing power dynamics between the global North and global South (also see Stoddart, 2012; Webb and Richelieu, 2016; Millington and Wilson, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in their own research on SDP organizations in Kingston, Jamaica, Darnell et al (2018a) found that an organization that had traditionally dealt with health and HIV/AIDS prevention turned its focus to sport when this opened up the possibility of obtaining funding and expertise from a UK-based international NGO. In effect, actors such as money, expertise, technical support, ‘and even the concept of sport’s development utility’ (Darnell et al, 2018a: 95) played a part in holding SDP together – and in revealing power dynamics between the global North and global South (also see Stoddart, 2012; Webb and Richelieu, 2016; Millington and Wilson, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SDP sector has (had to) become better at monitoring and evaluation and identify how they are 'making a difference' (Darnell, 2013;Donnelly, et al, 2011;Harris, 2018;Harris & Adams, 2016;Levermore, 2011;Nicholls, Giles & Sethna, 2010;Webb & Richelieu, 2016). However, for those working on ' sport-for-peace' initiatives there is a lack of consensus on what 'peace'…”
Section: Peacebuilding Conflict Resolution and Sport For Peacementioning
confidence: 99%
“…Rather than operate autonomously, organizations increasingly maintain a relationship with the state through various fiduciary or service provision relationships as government grants, service provision contracts, and public-private partnerships (King, 2006). These arrangements make NGOs more susceptible to external demands to adopt and internalize organizational practices of accountability and other measures of "proving worthiness" desired by today's funding and political bodies (Gordon, 2013;Webb & Richelieu, 2016 (Kwon, 2013;Baldridge, 2014;Kelly, 2012). For example, there is evidence that links operational insecurity to a tendency in organizations to overemphasize the dangers, inadequacies, and "riskiness" of youth when communicating with funders -a strategy that, while it may help to win funding, also diminishes the agency of youth, youth workers, and their communities (Baldridge, 2014), fuels processes of territorial stigmatization (Wacquant, 2008), and legitimizes intervention (Kelly, 2012).…”
Section: The Changing Context Of Community-based Youth Services Provisionmentioning
confidence: 99%
“…The "operational insecurity" (Kelly, 2012) and intense competition among youth organizations for funding has led to an increased focus on "proving worthiness." This involves proving that programs have the power to produce transformative change, as well as proving to funders that an organization is a worthy investment (Gordon, 2013;Webb & Richelieu, 2016).…”
Section: A Good Investment? Negotiating Constructions Of Successmentioning
confidence: 99%